Pengaruh Tata Kelola Perusahaan Dan Tanggung Jawab Lingkungan Terhadap Nilai Perusahaan: Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2016-2018 - Ahmad Faih (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2019)
This study aims to determine how corporate governance and environmental responsibility affect firm value and examine the correlation between corporate governance, environmental responsibility, and corporate value in Indonesia's country. This study's population are manufacturing companies listed on the Indonesia Stock Exchange (IDX) with the 2016-2018 observation period. The statistical test used is the classical assumption test to test the hypothesis using multiple regression analysis tests. The environmental responsibility data index obtains by analyzing the contents of the company's 2016-2018 annual report. The result of this research is that corporate governance affects environmental responsibility. This research contributes to the literature on social responsibility in developing countries, especially Indonesia, because in the era of globalization, Indonesia has begun to attract investment opportunities that will affect the environment in the long term.